Preliminary screening of endophytic fungi isolated from medicinal plants in MARDI Sessang, Sarawak for their bioactivity - Lim, Jeffrey Seng Heng; Radu, Son; Sadi, Tosiah (Malaysian Agricultural Research and Development Institute (MARDI), 2008)
A total of 100 isolates of endophytic fungi were isolated from 19 species of medicinal plants collected at MARDI Station Sessang, Sarawak. A total of 55% of the endophytic fungi were isolated from the leaves while 45% from the branches. Screening of isolates for enzymatic secretion found that 15, 28 and 12 isolates were able to hydrolyze cellulose, xylan and mannan respectively. All 100 isolates were also tested for their antimicrobial activity towards selected phytopathogenic and human pathogenic microbes. The test indicated that only one isolate showed positive result when tested against Xanthomonas campestris. The results indicate that the endophytic fungi isolated from medicinal plant at MARDI Research Station Sessang, Sarawak may have the potential to be further exploited for its bioactivity.